2013
DOI: 10.1088/0957-4484/24/25/255101
|View full text |Cite
|
Sign up to set email alerts
|

The anti-hepatoma effect of nanosized Mn–Zn ferrite magnetic fluid hyperthermia associated with radiationin vitroandin vivo

Abstract: Joint therapy is a promising area of study in cancer treatment. In this paper, we prepared Mn-Zn ferrite (Mn0.5Zn0.5Fe2O4) magnetofluid using PEI as a surfactant, and investigated the anticancer effect of Mn0.5Zn0.5Fe2O4 magnetic fluid hyperthermia (MFH) combined with radiotherapy on hepatocellular carcinoma. Both in vitro and in vivo results suggest that this combined treatment with MFH and radiation has a better therapeutic effect than either of them alone. The apoptotic rate and necrotic rate of the combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In clinical trials, Klaus et al used magnetic hyperthermia combined with radiotherapy to treat glioblastoma multiforme patients, and found that the combination therapy more effectively shrank tumours than either one of the therapies alone [45]. Using flow cytometry, we found that MNCs under an AMF displayed a slightly better killing effect than radiotherapy alone (at a dose of 4 Gy), while the group exposed to a combination of both treatments showed the highest apoptosis rate, which is consistent with the results reported by Lin et al [46]. The SER for CNE-2 and NCI-H460 cells was 1.35 and 1.44, respectively, confirming their radiosensitisation effect.…”
Section: Discussionsupporting
confidence: 91%
“…In clinical trials, Klaus et al used magnetic hyperthermia combined with radiotherapy to treat glioblastoma multiforme patients, and found that the combination therapy more effectively shrank tumours than either one of the therapies alone [45]. Using flow cytometry, we found that MNCs under an AMF displayed a slightly better killing effect than radiotherapy alone (at a dose of 4 Gy), while the group exposed to a combination of both treatments showed the highest apoptosis rate, which is consistent with the results reported by Lin et al [46]. The SER for CNE-2 and NCI-H460 cells was 1.35 and 1.44, respectively, confirming their radiosensitisation effect.…”
Section: Discussionsupporting
confidence: 91%
“…122 They chose a magnetic fluid with a NP concentration of 10 g/L because it stabilized around 43 °C under application of an AMF of frequency = 230 kHz and amplitude = 1 kA/m. Tumours were grown into the right posterior limb rump of nude mice by injecting exponentially growing HepG2 cells.…”
Section: Examples Of In Vivo Applications Hyperthermia Therapymentioning
confidence: 99%
“…It therefore leads to increasing thermomagnetic coefficient 49,50 (݇ ்ெ = −∆ߪ ∆ܶ ⁄ , where ߪ is the magnetization per unit mass) and decreasing Curie temperature hence limiting the upper temperature reached by MFH to the safety range (41 -45 o C) [49][50][51][52][53][54] . This characteristic would be very promising because it could enable a local self-regulated temperature control 55,56 , which would avoid damages to healthy tissues due to overheating.…”
mentioning
confidence: 99%